Therapeutic Effects of Low Level Laser Therapy (LLLT) in Knee Osteoarthritis, Compared to Therapeutic Ultrasound - Rayegani, Seyed Mansour; Bahrami, Mohammad Hasan; Elyaspour, Darioush; Saeidi, Mahdi; Sanjari, Hosein (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Low-level laser therapy (LLLT) is thought to have analgesic and biomodulatory effects. Our objective was to assess the pain-relieving effect of LLLT and possible changes in joint stiffness and disability of patients with knee osteoarthritis (KOA) and compare it to the more commonly used modality; therapeutic ultrasound(US). METHODS: 37 patients with mild or moderate KOA were randomized to receive either LLLT, placebo LLLT or US. All patients received a common treatment including acetaminophen (up to 2gr/d) and medical advices for lifestyle modification and exercise. Treatments were delivered 5 times a week over a period of 2 weeks. Active laser group was treated with a diode laser (wavelength 880 nm, continuous wave, power 50 mW) at a dose of 6 J/point (24 J/knee). The placebo control group was treated with an ineffective probe (power 0 mW) of the same appearance. The third group received pulsed ultrasound with an intensity of 1.5-2 w/cm2, and for 5 minutes per knee. Visual Analogue Scale (VAS) and Western Ontario MacMaster (WOMAC) questionnaires were used for data gathering before,1 and 3 months after completing the therapy. RESULTS: Pain reduced in all 3 groups but laser was superior in comparison. Stiffness improved 1 mo after therapy in the laser group but not in the others. Disability decreased in both laser and US groups (more significantly in the laser group) but not in the placebo group. CONCLUSION: Our results show that LLLT reduces pain, joint stiffness and disability in KOA and is superior to placebo and US.